A Lie Algebroid on the Wiener Space. (21st January 2010) - Léandre, Rémi
Abstract : We define a Lie algebroid on the space of smooth 1-forms in the Nualart-Pardoux sense on the Wiener space associated to the stochastic linear Poisson structure on the Wiener space defined Léandre (2009).